Subcutaneous immunoglobulin in responders to intravenous therapy with chronic inflammatory demyelinating polyradiculoneuropathy. Issue 5 (7th January 2013) - Markvardsen, L. H.; Debost, J.‐C.; Harbo, T.; Sindrup, S. H.; Andersen, H.; Christiansen, I.; Otto, M.; Olsen, N. K.; Lassen, L. L.; Jakobsen, J.; ,
<x xml:space="preserve">Abstract</x> Background and purpose We hypothesized that subcutaneous administration of immunoglobulins (SCIG) in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is feasible, safe and superior to treatment with saline for the performance of muscle strength. Methods Thirty patients with motor involvement in maintenance therapy with intravenous immunoglobulin (IVIG) fulfilling the EFNS/PNS criteria for CIDP, aged 18–80 years, were randomized either to SCIG at a dose corresponding to their pre‐study IVIG dose or to subcutaneous saline given twice or thrice weekly for 12 weeks at home. At the start and end of the trial as well as 2 weeks before (−2, 0, 10, 12 weeks), isokinetic strength performance of four predetermined and weakened muscle groups was measured. Also, an Overall Disability Sum Score (ODSS), 40‐m‐walking test (40‐MWT), nine‐hole‐peg test, Neurological Impairment Score (NIS), Medical Research Council (MRC) score, grip strength, standardized electrophysiological recordings from three nerves, and plasma IgG levels were evaluated. Results SCIG treatment was well tolerated in all 14 patients. Six patients complained of mild side‐effects at the injection site. In the SCIG group there was an increase of isokinetic muscle strength of 5.5 ± 9.5% (P < 0.05) as compared with a decline of 14.4 ± 20.3% (P < 0.05) in the placebo group; the difference between the two groups being significant (P < 0.01). ODSS, NIS, MRC, grip strength and 40‐MWT improved following SCIG versus saline. Conclusions SCIG treatment in CIDP is feasible, safe and effective, and seems an attractive alternative to IVIG.